Regulation of trehalose metabolism by Streptomyces griseus spores. - McBride, M J (1990)
Spores of Streptomyces griseus contain trehalose and trehalase, but trehalose is not readily hydrolyzed until spore germination is initiated. Trehalase in crude extracts of spores, germinated spores, and mycelia of S. griseus had a pH optimum of approximately 6.2, had a Km value for trehalose of approximately 11 mM, and was most active in buffers having ionic strengths of 50 to 200 mM. Inhibitors or activators or trehalase activity were not detected in extracts of spores or mycelia. Several lines of evidence indicated that trehalose and trehalase are both located in the spore cytoplasm. Spores retained their trehalose and most of their trehalase activity following brief exposure to dilute acid. Protoplasts formed by enzymatic removal of the spore walls in buffer containing high concentrations of solutes also retained their trehalose and trehalase activity. Protoplasts formed in buffer containing lower levels of solutes contained low levels of trehalose. The mechanism by which trehalose metabolism is regulated in S. griseus spores is unresolved. A low level of hydration of the cytoplasm of the dormant spores and an increased level of hydration during germination may account for the apparent inactivity of trehalase in dormant spores and the rapid hydrolysis of trehalose upon initiation of germination.